1998
DOI: 10.1023/a:1024496427434
|View full text |Cite
|
Sign up to set email alerts
|

“Seeking safety”: Outcome of a new cognitive‐behavioral psychotherapy for women with posttraumatic stress disorder and substance dependence

Abstract: Women with current posttraumatic stress disorder (PTSD) comprise 30-59% of substance abuse treatment samples and experience a more severe course than women with either disorder alone. As yet, no effective treatment for this population has been identified. This paper reports outcome results on 17 women who completed a new manual-based 24-session cognitive behavioral group therapy protocol treatment, based on assessments at pretreatment, during treatment, posttreatment, and at 3-month follow-up. Results showed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
281
1
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 393 publications
(303 citation statements)
references
References 36 publications
12
281
1
8
Order By: Relevance
“…A number of studies have demonstrated the effectiveness of gender-specific treatment as it relates to the specialized needs of substance-using women (Elk et al, 1995;Hien et al, 2004;Jansson et al, 1996;Kelly et al, 2000;Linehan et al, 1999;Luthar and Suchman, 2000;Mackie-Ramos and Rice, 1988;Najavits et al, 1998;Reynolds et al, 1995;Volpicelli et al, 2000;Washington, 2001;Welle et al, 1998). These studies have examined services to address psychosocial needs that are more prevalent in women, as well as certain subpopulations, or specialized interventions for a particular subgroup of women.…”
Section: Gender-specific Treatment and Its Relationship To Special Nementioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have demonstrated the effectiveness of gender-specific treatment as it relates to the specialized needs of substance-using women (Elk et al, 1995;Hien et al, 2004;Jansson et al, 1996;Kelly et al, 2000;Linehan et al, 1999;Luthar and Suchman, 2000;Mackie-Ramos and Rice, 1988;Najavits et al, 1998;Reynolds et al, 1995;Volpicelli et al, 2000;Washington, 2001;Welle et al, 1998). These studies have examined services to address psychosocial needs that are more prevalent in women, as well as certain subpopulations, or specialized interventions for a particular subgroup of women.…”
Section: Gender-specific Treatment and Its Relationship To Special Nementioning
confidence: 99%
“…A study that examined the specialized treatment needs of substance-abusing women with PTSD (Najavits et al, 1998) reviewed outcome data for Seeking Safety, a cognitive-behavioral group intervention designed specifically for this population. Psychosocial assessments found significant improvements post treatment and at follow-up in a variety of domains, including increased substance abstinence, decreased subtle trauma symptoms, decreased depression, and decreased suicidal thoughts and risk (not assessed at follow-up).…”
Section: Gender-specific Treatment and Its Relationship To Special Nementioning
confidence: 99%
See 1 more Smart Citation
“…Integrated PTSD and SUD treatments are increasingly being implemented in community substance abuse treatment programs (Brady et al, 2001;Finkelstein et al, 2004 ;Hien et al, 2004 ;Najavits et al, 1998 ). There is a general consensus in the literature that, despite concerns over adverse reactions or negative experiences attributed to treatment, patients who do engage in non-psychopharmacological interventions see significant improvements in PTSD symptoms (Seedat et.al., 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Somit könnte eine frühe Behandlung der traumatischen Ereignisse die Chancen für eine erfolgreiche Drogentherapie erhöhen (Ouimette, Ahrens & Moos 1997). Auch könnten einige der bestehenden Behandlungsmethoden für PTBS allein und Drogenabhängigkeit allein problematisch sein, wenn die jeweils andere Störung unbehandelt weiterbesteht (Najavits, Weiss, Shaw & Muenz, 1998). …”
Section: Theoretischer Und Empirischer Hintergrundunclassified